1995
DOI: 10.1007/bf00365566
|View full text |Cite
|
Sign up to set email alerts
|

High mortality, fluctuation in numbers, and heavy subterranean insect herbivory in bush lupine, Lupinus arboreus

Abstract: Sporadic patchy die-off of bush lupine, Lupinus arboreus, has long been known. We describe in detail a series of these incidents on the central California coast, based upon observational and comparative evidence. Stands of thousands of plants die, while nearby mature plants live on. In some sites, repeated die-off followed by regeneration from the seed bank has led to the cover and density of this woody, perennial plant fluctuating widely over the 40 year period for which records exist. Root damage by caterpil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
101
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(105 citation statements)
references
References 13 publications
3
101
1
Order By: Relevance
“…Bayshore (BS) and Mussel Point (MP) are grassland sites. At Bayshore, cover and persistence of bush lupine is highly variable, with average lupine cover fluctuating from 0 to 60% over 10-year periods (Strong et al, 1995). Fluctuations in cover may be caused by high rates of herbivore damage; stands with little fluctuation in lupine cover had the fewest Hepialus caterpillars per root (Strong et al, 1995;Maron, 1998;.…”
Section: Study Organism and Sitesmentioning
confidence: 99%
See 3 more Smart Citations
“…Bayshore (BS) and Mussel Point (MP) are grassland sites. At Bayshore, cover and persistence of bush lupine is highly variable, with average lupine cover fluctuating from 0 to 60% over 10-year periods (Strong et al, 1995). Fluctuations in cover may be caused by high rates of herbivore damage; stands with little fluctuation in lupine cover had the fewest Hepialus caterpillars per root (Strong et al, 1995;Maron, 1998;.…”
Section: Study Organism and Sitesmentioning
confidence: 99%
“…While one or two herbivores might have the largest effects on plant fitness, most plants suffer from herbivores representing many different guilds, including leaf feeders, gallers, stem borers, or seed predators. The role of defensive compounds against leaf feeding herbivores has received the most attention (Rosenthal and Berenbaum, 1991), although guilds of herbivores such as root borers (Brown, 1988;Strong et al, 1995;Maron, 1998), seed predators (Louda and Potvin, 1995) and apical meristem feeders (Juenger and Bergelson, 1997) may also have strong fitness effects. For example, Strong et al (1995) found a positive correlation between the number of root boring Hepialus californicus larvae and the rate of lupine mortality, and decreases of H. californicus densities by half led to a 44% increase in lupine seed set (Preisser, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In grasslands, lupine populations often fluctuate dramatically. In some grassland sites, lupine populations oscillate from Ͻ5% to 75% cover (Strong et al 1995;pers. obs.).…”
mentioning
confidence: 99%